Molecular docking and ADMET studies of the Interaction of 4-carboxyl-2,6-dinitrophenylazohydroxynaphthalenes with Bovine Serum Albumin (2023)
Previous spectrophotometric investigations revealed strong binding affinities between four potential monoazo colourants (code-named AZ-01 to 04) and bovine serum albumin (BSA) which could dictate the tissue distribution and toxicity of the additives. The molecular docking interactions of the dyes with BSA were analyzed using AutoDock vina and PatchDock in order to elucidate the functional groups involved in complex stabilization. Docking conformations confirmed the ligands preferentially inserted into the hydrophobic cavities of BSA site I. Structure-BSA binding relationships revealed the binding of AZ-02 was driven by hydrogen bond donation from its free phydroxynaphthalene substituent to Ser-479 while the predominantly hydrazone form of its positional isomer, AZ-01, increased its lipophilicity and tendency for hydrophobic interactions. The relatively higher C/H ratio of AZ-03 and -04, which contain additional C-7 substituents, was responsible for their stronger binding and the extensive involvement of their aromatic rings in ligand-site I complex stabilization via Pi-Pi T-shaped, Pi-alkyl and alkyl-alkyl interactions. Moreso, AZ-01, -03 and -04 exist predominantly as hydrazone tautomers with an overall positive charge which provided complementary modes for interaction with negatively charged aspartic and glutamic acids. The structure-BSA binding relationships of the molecules, which can be employed in synthesis of safer congeners, have been elucidated.